Comparative Study on Udder and Teat of Desi and Crossbred Cows in Relation to Udder Immunity - Paul, Susanta; Das, Partha; Ghosh, Ranjit Kumar (Indian Journal of Veterinary Anatomy, 2013)
The present study was conducted on 120 desi (Indian zebu) and crossbred cows in terms of the various characteristics of udder and teat. The occurrence of trough shaped udder was higher in desi cow as compared to the crossbred cow whereas, pendulous udder was recorded maximum in case of crossbred cow. The incidence of tight udder attachment, deep udder cleft, balanced udder quarters were higher in desi cows. The occurrence of closer teat placement, cylindrical teats and pointed teat end were comparatively higher in desi cows.